A comprehensive review on plant protein-based food packaging: Beyond petroleum-based polymers - Subhash V. Pawde; Pimonpan Kaewprachu; Passakorn Kingwascharapong; Samart Sai-Ut; Thomas Karbowiak; Young Hoon Jung; Saroat Rawdkuen (Current Research in Food Science)
In the era of biodegradable packaging, protein-based biopolymers have emerged as a sustainable alternative to petroleum-based polymers due to their unique properties. Despite significant advances in this field, a comprehensive analysis of recent technological innovations with commercial viability assessments remains lacking. This review addressed this gap by systematically examining recent lab development in plant protein-based packaging, including sources, fabrication methods, real-time applications, commercial challenges, and their relationship to food packaging applications. Through analysis of recent studies, 2020–2025, we identify recent research trends that have focused on enhancing the properties of biodegradable polymers by incorporating antimicrobial, insecticidal, and antifungal agents, thereby creating active systems to prolong the shelf life of foods. Furthermore, our critical evaluation of advancements in fabrication techniques such as 3D printing, electrospinning, co-polymerization, casting, molding, extrusion, and coating has enabled the production of protein-based packaging with diverse shapes and properties. This review uniquely bridges the gap between laboratory innovations and commercial applications by examining current trends in sources, functions, applications, and future commercial challenges associated with plant protein-based packaging. By understanding the potential of these biopolymers, we can contribute to the development of sustainable and innovative packaging solutions within the food industries, offering a roadmap for both researchers and industry stakeholders.